ASUHAN KEBIDANAN PADA IBU NIFAS NY”E” P2A0H2 DI RUMAH BERSALIN BUNDA PUJATEMBILAHAN TAHUN 2019 - Yolanda Novitri; Madinah (STIKES HUSADA GEMILANG, 2021)
Approximately 60% of maternal deaths occur after childbirth and nearly 50% of it happened in the first 24 hours after childbirth. The total of post-partum mothers at the Bunda Puja Maternity Hospital Tembilahan were 271 people which from January to December 2019 was 195, and January to July 2020 was 76. The aim of this care is to provide midwifery care for Mrs.